EDUKASI MENGELOLA KEINGINAN DAN KEBUTUHAN MELALUI MENABUNG PADA SISWA SDN PANYAWEUYAN - Rahmah, Azkia; Iriani Roesmala Dewi, Fransisca; Salsabila; Yehezkiel, Renshi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2025)
ABSTRACT Saving activities are important to form habits in managing positive finances, it is highly recommended to be taught to children from an early age. The habit of saving for children is not only to save money, but saving also involves the process of learning to manage finances, self-control, and planning for the future. By saving children, they become more responsible and do not have a consumptive nature. The purpose of this activity is to teach 4th grade students of SDN Panyaweuyan about the importance of saving as a form of self-control and being able to distinguish between wants and needs in using their pocket money. This activity was carried out on February 24, 2025 and was attended by 32 students from grade 4 of SDN Panyaweuyan. To determine the success of this activity, the implementation team conducted measurements using a qualitative approach with random interview observation and a quantitative approach with questionnaires. Observations that have been made show that saving at school is not the desire of students, but the initiative of the students' parents. The activity began with a pre-test using the adaptation of the Brief Self-Control Scale (BSCS) measuring tool using a likert scale for 30 minutes. Next, socialization about the difference between wants and needs, followed by the game